The Effect Of Financial Literacy, Lifestyle And Parental Income On The Financial Behavior Of UNPAB Students Receive Bank Indonesia Scholarships - Gunawan, Slamet; Hernawaty, Hernawaty (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of financial literacy, lifestyle and parental income on the financial behavior of UNPAB students receiving Bank Indonesia Scholarships. The research approach used is quantitative. The research was conducted at Universitas Pembangunan Panca Budi (UNPAB) which is located at Jl. Jend. Gatot Subroto Km.4.5 Sei Sikambing, Medan, North Sumatra. The sample used was 50 respondents. The analysis technique used in this research is multiple linear regression analysis. The results of this study are Financial Literacy (), Lifestyle () and Parental Income () simultaneously have a positive and significant effect on the Financial Behavior of UNPAB Students who receive Bank Indonesia Scholarships.